Empirical Study of the Student’s Communicative-Speech Styles - Tsos, Yulia (Psychological Prospects Journal, 2016)
The article presents the results of empirical research of student’s communicativespeech styles. The percentiles of the distribution of data psycholinguistic markers to define groups of subjects, respectively, to the manifestation of different communicative speech styles have been determined. Based on the results of the analysis frequency, the maximum and minimum values of the parametric variables, and qualitative analysis of nonparametric variables have been allocated to 9 groups of subjects with a combined indirect, combined direct, combined elaborate, combined (direct/indirect, elaborat/succinct), direct elaborate, direct succinct, combined succinct, indirect succinct, indirect elaborate styles. To verify the reliability of the selected groups the procedure of discriminant analysis have been use. This analysis allowed us to solve two problems: to interpret the differences between the selected groups of subjects and to confirm the classification of the communicative-speech style depending on discriminating variables. Using data analysis canonical function of the group with the highest density of the object: combination (direct/indirect, elaborate/succinct), direct elaborate, direct succinct, indirect succinct, indirect elaborate have been allocated. The percentage distribution of the subjects in all groups has been graphically showed. Each of these styles differently correlated with styles of activities, emotional and motivational styles in the general personality style organization. Thus, the communicative-speech styles are inextricably linked to personal properties.Keywords: communicative-speech style, psycholinguistic markers, percentile, discriminant analysis, personal characteristics.